2021
DOI: 10.1039/d1ra06914d
|View full text |Cite
|
Sign up to set email alerts
|

Rice husk biochar modified-CuCo2O4 as an efficient peroxymonosulfate activator for non-radical degradation of organic pollutants from aqueous environment

Abstract: A series of rice husk biochar (RHBC) modified bimetallic oxides were prepared using a simple pyrolysis method to activate peroxymonosulfate (PMS) for the degradation of acid orange G (OG).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Like these carbon materials, biochar has shown its potential in electron donation and transfer in AOPs, but the specic routes are different for the biochars prepared at different conditions. For example, Wang et al 29 and Hong et al 34 have proposed that PFRs in the biochar prepared at 500 C were the dominant electron donors to reduce Fe(III) for activation of persulfates. However, our previous study has shown that the biochar prepared at 700 C was more reactive on facilitating the Fe(III)/Fe(II) cycle in Fenton process, 20 although Yang et al 58 and Zeng et al 30 have reported that there are few PFRs in the biochar prepared at 700 C. Therefore, PFRs are not likely to be the major electron donors for reduction of Fe(III) in this study.…”
Section: Interactions Between Dissolved Fe(iii) and Biocharmentioning
confidence: 99%
See 1 more Smart Citation
“…Like these carbon materials, biochar has shown its potential in electron donation and transfer in AOPs, but the specic routes are different for the biochars prepared at different conditions. For example, Wang et al 29 and Hong et al 34 have proposed that PFRs in the biochar prepared at 500 C were the dominant electron donors to reduce Fe(III) for activation of persulfates. However, our previous study has shown that the biochar prepared at 700 C was more reactive on facilitating the Fe(III)/Fe(II) cycle in Fenton process, 20 although Yang et al 58 and Zeng et al 30 have reported that there are few PFRs in the biochar prepared at 700 C. Therefore, PFRs are not likely to be the major electron donors for reduction of Fe(III) in this study.…”
Section: Interactions Between Dissolved Fe(iii) and Biocharmentioning
confidence: 99%
“…Herein, we hypothesize that the H 2 O 2 activation by biochar can be enhanced by using trace dissolved iron (Fe) together. Biochar, being an electron-rich and conductive carbon material, can act as a reductant of Fe(III) for persulfate activation to enhance the degradation of organic pollutants, 29,30 and can also accelerate Fe(III)/Fe(II) cycle that is the rate-limiting step in Fenton and Fenton-like processes. 31,32 Thereby, the required dosage of Fe(II) in Fenton process can be diminished substantially by biochar, 20 which is benecial for minimizing the production of iron sludge that is still a challenge in Fenton process.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative to face this concern, the rice husk can be used as a precursor for the preparation of PCMs with and without metal charge. PCM from rice husk has been used as an activator of PDS and PMS for the removal of organic pollutants in water such as phenols (Hussain et al 2017 ; Liu et al 2021 ; Zhang et al 2022 ), esters (Dong et al 2019 ), dyes (Li et al 2020 ; Xie et al 2021 ), and pharmaceuticals (Avramiotis et al 2021a , b ; Xie et al 2021 ). Indeed, biochar from rice husk modified with FeCl 3 has been tested for PMS activation and bisphenol A elimination through radical pathways where competing effects by the matrix components were observed (Gao et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%